Case Report: Extrinsic Compression of the Left Main Coronary Artery by a Giant Sinus of Valsalva Aneurysm - Ning, Feifei; Tang, Manyun; Wang, Mengjie; Muhlestein, Joseph B.; Day, John D.; Li, Guoliang; Yan, Yang (Frontiers in Cardiovascular Medicine, 2021)
Sinus of Valsalva aneurysm (SoVA) is an uncommon clinical entity, which is present in roughly 0.09% of the general population. The cause can be either acquired or congenital. Clinically SoVA of unruptured status are hardly captured even diagnosed due to atypical clinical presentations. Here we present a rare case of exertional angina pectoris and recurrent syncope due to an extrinsically compressed left coronary artery by a gaint SoVA in a 50-year-old female patient, which was successfully repaired by surgical exclusion and was still doing well after two years of follow-up. In a word, the clinical presentations, precise imaging and anatomy proof and effective surgical treatment make the case extremely rare and interesting.